Gender differences and predictors of the impact of self-regulated learning in physical education on muscle strengthening in adolescents - Bujosa-Quetglas, Guillem; Vidal-Conti, Josep (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Low participation in muscle-strengthening physical activity (MSPA), especially among adolescent girls, highlights the importance of self-regulation in fostering this habit. Given the importance of self-efficacy for adolescent physical education students in initiating and maintaining healthy physical activity habits, this study explored how variables from Zimmerman’s model (self-efficacy, planning, self-control, effort, evaluation, and reflection) relate to gender and affect participants’ reported levels of healthy physical activity habits. Zimmerman’s self-regulated learning (SRL) model was implemented in 295 adolescents (12-17 years; M = 14.2, SD = 1.47; 53.9 % male, 46.1 % female). The cross-sectional study assessed SRL and MSPA using specific questionnaires. Significant differences were found in self-efficacy (p = 0.008), effort (p < 0.001) and self-reflection (p = 0.014), with higher scores in men, whereas the total self-regulation score favoured women (p = 0.035). Higher MSPA levels were associated with higher SRL scores across all dimensions of SRL: self-efficacy (ε² = 0.1893), planning (ε² = 0.0957), effort (ε² = 0.1821), self-control (ε² = 0.0808), evaluation (ε² = 0.1057), reflection (ε² = 0.1367) and total self-regulation score (ε² = 0.184). The model explained 20.9 % of the variability in MSPA, with self-efficacy (p = 0.006) and effort (p = 0.034) as significant predictors. The study underscores the need to integrate SRL into MSPA-promoting educational interventions using inclusive approaches and explicit instruction.